Pencirian proses penyediaan titanium silisida untuk kegunaan saling hubung litar bersepadu CMOS - Uda Hashim,; Burhanuddin Yeop Majlis,; Sahbudin Shaari, (2000)
Characterization of the titanium silicide process preparation for the application of interconnection in CMOS integrated circuit has been characterized. The process characterize are titanium deposition, selective wet etching, native oxide removal and thermal budget adjustment of reflow- anneal borophosphosilicate glass. Titanium film was sputter-deposited at various times by PVD system. The relationship between titanium deposition time and film thickness is plotted. The relation Y = 3.8X0.89 which was generated by the graph is employed to determine deposition time at any specific thickness. The solution which is the mixture of NH4OH, 30% H2O2, H2O (1:1:5) for solution 1, H2SO4 10% HF, H2O (30:1:69) for solution 2, and H2SO4 30% H2O2 (1: 1) for solution 3 have been tested for titanium selectivity wet etching. Base on the calculation, the etching rate of the solution 1, 2, and 3 are 0.15 nm/s, 7.8 nm/s and 1.16 nm/s, respectively. The wafer, which is dipped in the HF solution before titanium deposition revealing a better silicide/silicon, interface after heat treatment process. The reduction thermal budget of BPSG reflow-anneal from 900°C to 850°C for 30 minutes using furnace couple with additional anneal at 950°C for 60 seconds rapid 60 seconds rapid thermal annealer revealed the same surface topography with the wafer that annealed at 900°C for 30 minutes using conventional furnace